2018
DOI: 10.1093/rb/rby006
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular stent-induced alterations in host artery mechanical environments and their roles in stent restenosis and late thrombosis

Abstract: Cardiovascular stent restenosis remains a major challenge in interventional treatment of cardiovascular occlusive disease. Although the changes in arterial mechanical environment due to stent implantation are the main causes of the initiation of restenosis and thrombosis, the mechanisms that cause this initiation are still not fully understood. In this article, we reviewed the studies on the issue of stent-induced alterations in arterial mechanical environment and discussed their roles in stent restenosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 95 publications
0
40
0
Order By: Relevance
“…Besides common risk factors related to a patient’s pathological characteristics, such as disease history, smoking, and diabetes mellitus, some lesion-specific factors, including a longer lesion length and smaller vessel diameter, are potential risks of ISR 19 , 20 . Furthermore, as shown in previous studies on different vascular regions, in particular coronary arteries, the implantation of a stent within an artery alters the local hemodynamics, resulting in stagnation, recirculating flow, and areas subjected to low wall shear stress (WSS) 21 , which may promote the ISR development 22 , 23 . Recently, computational fluid dynamics (CFD) tools have been used to investigate the relationship between altered hemodynamics and restenosis in femoropopliteal artery atherosclerotic lesions treated with angioplasty or stenting 24 .…”
Section: Introductionmentioning
confidence: 97%
“…Besides common risk factors related to a patient’s pathological characteristics, such as disease history, smoking, and diabetes mellitus, some lesion-specific factors, including a longer lesion length and smaller vessel diameter, are potential risks of ISR 19 , 20 . Furthermore, as shown in previous studies on different vascular regions, in particular coronary arteries, the implantation of a stent within an artery alters the local hemodynamics, resulting in stagnation, recirculating flow, and areas subjected to low wall shear stress (WSS) 21 , which may promote the ISR development 22 , 23 . Recently, computational fluid dynamics (CFD) tools have been used to investigate the relationship between altered hemodynamics and restenosis in femoropopliteal artery atherosclerotic lesions treated with angioplasty or stenting 24 .…”
Section: Introductionmentioning
confidence: 97%
“…The complete re-endothelialization of the stent surface, therefore, is the key to the success of the stent-implantation [ 37 ]. Drug-eluting stents non-selectively inhibit smooth muscle tissue proliferation and the endothelialization process on the surface of the stent, which is likely to cause the severe side effect of late thrombosis [ 38 ]. Therefore, drawing on the lessons of drug-eluting stents, the new generation of stents should suppress the growth of SMCs while minimizing the inhibition of ECs growth.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…By placing undersized stent at the lesion site or insufficient expansion, it was found that upstream of the stent induced high shear stress while the downstream produced low shear stress (Rikhtegar et al, 2014). Wang et al (2018) indicated that low WSS was usually observed at the distal of the stent struts as compared with the proximal end of the struts. Using an in vitro flow chamber that contained ridges, Hsiao et al (2016) indicated that flow rate of 21.6 ml/min medium would generate flow velocities that were the highest through the center (0.25 m/s).…”
Section: Discussionmentioning
confidence: 99%